Rapid discontinuation of prednisone in kidney transplant recipients from at‐risk subgroups: an OPTN/SRTR analysis. (24th October 2019) - Vock, David M.; Matas, Arthur J.
Summary: Although rapid discontinuation of prednisone (RDP) after kidney transplantation has been successful in low‐risk recipients, there is concern about RDP use in recipients at increased risk for rejection or recurrent disease. Using SRTR, we compared outcomes for RDP versus maintenance prednisone‐treated recipients for all  adult 1st and 2nd transplants ( n  = 169 479) and the following 1st transplant subgroups: African American (AA); highly sensitized; those with a potentially recurrent disease; and pediatric recipients. For all adult 1st LD and DD transplants, RDP was associated with better patient and graft survival. For all LD subgroups, RDP and maintenance prednisone were associated with similar patient, graft, and death‐censored (DC) graft survival. For 1st transplant DD subgroups, RDP was associated with better patient survival in AA, those with potentially recurrent disease, and pediatric recipients; graft survival with RDP was better in AAs. For adult 2nd DD transplants, RDP was associated with worse DC‐graft survival. Importantly, for all differences, the effect size was small. With the exception of 2nd DD transplants, RDP protocols can be used without decreasing patient or graft survival for subgroups of 1st DD and LD kidney transplant recipients and for 2nd LD transplant recipients, at increased risk of rejection or recurrent disease.